Relationship of Sociodemographic Variables and Psychosocial Stressors in Dissociative(Conversion) Disorder Patients - Mazhar Malik, Fatima Bilal, Farkhanda Jabeen, Sajida Kazmi (Journal of Rawalpindi Medical College, 2011)
Background: To assess the relationship of sociodemographic variables with the psychosocial stressors in dissociative (conversion) disorder patients. Metohds: A descriptive cross-sectional study was carried out on 100 diagnosed patients of conversion disorder. Participating patients underwent detailed assessment which included, application of consent form, physical examination, ICD-10 criteria of conversion disorder, demographic profile assessment and psychosocial assessment based on 1CD-10. Results: Majority of the patients were young, female, formally educated, rural residents, unmarried and were unemployed. Among all variables only adolescent patients between age of 13-19 years were having problems associated with education and literacy and all others were facing difficulties associated with primary support group. p value of significance(<0.05) was found to be non significant in all the variables. Conclusion: Majority of the patients have difficulties with primary support group including family circumstances